STUDI ADAPTASI IKAN BILEH (Rasbora sp.) YANG BERASAL DARI DANAU IE SAYANG SEBAGAI TAHAP AWAL DOMESTIKASI - Rahmayanti, Fitria; Najmi, Nurul; Islama, Dini; Muliyana, Agusriati (JURNAL AKUAKULTURA, 2021)
Bileh (Rasbora sp.) is a fish with high economic value. So that, the population was decline in its natural habitat due to exploitation activities and environmental perturbation due to human activities. As an action to avoid this fish from extinction, it is necessary to apply domestication activities. This study was conducted to determine the adaptability of bileh fish from Lake Ie Sayang in culture container. The information of this study can be used as an early information for the domestication development of bileh fish. Total each 30 fishes from Lake Ie Sayang are culture in three 10 liter plastic containers. Fish were reared for 28 days and observed the survival rate and mortality of fish per week. Water quality parameters measured include temperature, dissolved oxygen (DO) and pH. The results showed that the fish were able to adapt in the rearing container with the survival and mortality rates at the end of the rearing 63.33% and 34.44%, respectively. Water quality parameters during the study namely temperature 27 oC, DO 5.2 ppm and pH 6.8.